Evaluation of Patient’s Aesthetic Satisfaction after the Cementation of the Porcelain Fused to Metal Crown - Lubna Memon, Ziaullah Choudhry, Kashif Aslam, Sofia Malik, H R Sukhia, Anwar Ali, M. Adeel Ahmed, Rizwan Jouhar, Fahim Vohra (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To assess the aesthetic satisfaction with the metal-ceramic dental prosthesis in relation to patient education, age and gender. Methods: This prospective longitudinal study was undertaken by selecting 360 adult patients from both genders indicated for single maxillary porcelain fused to metal crowns. These patients were categorized into three groups based on gender, age, and education. Patients were assessed for aesthetic satisfaction for tooth shape; color, angulation, visibility, and shade at the time of insertion and at a follow-up of 12 weeks. At the time of the prosthesis insertion, a self-evaluation questionnaire was provided to each patient to record their satisfaction levels with the prosthesis. Satisfaction levels among the participants were evaluated based on participants’ age, gender, and education level (Chi-square). A p-value of 0.05 was considered statistically significant. Results: The study enrolled 150(41.67%) males and 210(58.33%) females with the participant age ranging from 19 to 60 years and a mean age of 30.53 (± 10.88 years). 84(23.3%) were uneducated participants, 210(58.3%) were high school graduates, and 66(18.3%) were university graduates. A decrease in the level of satisfaction was observed with increasing years of patient education at insertion. The overall aesthetic satisfaction among patients at PFM crown insertion (65%) and at 12 weeks follow-up (69.2%) was statistically comparable (p>0.05). Practical implication: Aesthetic is the most important consideration for the replacement of anterior teeth. Numerous studies evaluated the aesthetic satisfaction of the patients after providing full ceramic prosthesis, however, data regarding patient satisfaction after the metal ceramic dental prosthesisis scarce in the scientific literature. Conclusion: Satisfaction with the esthetic restoration depends on patient education and awareness. Age and education add to a person’s experience and increase awareness with respect to better aesthetics. Keywords: Aesthetics; patient satisfaction; assessment; patient care, metal ceramic prosthesis